Case Report: A de novo Variant of CRYGC Gene Associated With Congenital Cataract and Microphthalmia - Peng, Yu; Zheng, Yu; Deng, Zifeng; Zhang, Shuju; Tan, Yilan; Hu, Zhengmao; Tao, Lijuan; Luo, Yulin (Frontiers in Genetics, 2022)
Background: Congenital cataract is one of the most common causes of blindness in children. A rapid and accurate genetic diagnosis benefit the patients in the pediatric department. The current study aims to identify the genetic defects in a congenital cataract patient without a family history. Case presentation: A congenital cataract patient with microphthalmia and nystagmus was recruited for this study. Trio-based whole-exome sequencing revealed a de novo variant (c.394delG, p.V132Sfs*15) in CRYGC gene. According to the American College of Medical Genetics and Genomics (ACMG) criteria, the variant could be annontated as pathogenic. Conclusion: Our findings provide new knowledge of the variant spectrum of CRYGC gene and are essential for understanding the heterogeneity of cataracts in the Chinese population.